Potential alien ranges of European plants will shrink in the future, but less so for already naturalized than for not yet naturalized species. Issue 11 (26th July 2021) - Pouteau, Robin; Biurrun, Idoia; Brunel, Caroline; Chytrý, Milan; Dawson, Wayne; Essl, Franz; Fristoe, Trevor; Haveman, Rense; Hobohm, Carsten; Jansen, Florian; Kreft, Holger; Lenoir, Jonathan; et al.
Abstract: Aims: The rapid increase in the number of species that have naturalized beyond their native range is among the most apparent features of the Anthropocene. How alien species will respond to other processes of future global changes is an emerging concern and remains poorly misunderstood. We therefore ask whether naturalized species will respond to climate and land use change differently than those species not yet naturalized anywhere in the world. Location: Global. Methods: We investigated future changes in the potential alien range of vascular plant species endemic to Europe that are either naturalized ( n  = 272) or not yet naturalized (1, 213) outside of Europe. Potential ranges were estimated based on projections of species distribution models using 20 future climate‐change scenarios. We mapped current and future global centres of naturalization risk. We also analysed expected changes in latitudinal, elevational and areal extent of species' potential alien ranges. Results: We showed a large potential for more worldwide naturalizations of European plants currently and in the future. The centres of naturalization risk for naturalized and non‐naturalized plants largely overlapped, and their location did not change much under projected future climates. Nevertheless, naturalized plants had their potential range shifting poleward over larger distances, whereas the non‐naturalized ones had their potential elevational ranges shifting further upslope under the most severe climate change scenarios. As a result, climate and land use changes are predicted to shrink the potential alien range of European plants, but less so for already naturalized than for non‐naturalized species. Main conclusions: While currently non‐naturalized plants originate frequently from mountain ranges or boreal and Mediterranean biomes in Europe, the naturalized ones usually occur at low elevations, close to human centres of activities. As the latter are expected to increase worldwide, this could explain why the potential alien range of already naturalized plants will shrink less.